Lower Jurassic calcareous nannofossil taxonomy revisited according to the Neuquén Basin (Argentina) record - Chaumeil Rodríguez, Micaela (2022)
Standard Early Jurassic biostratigraphic studies were performed in the boreal and Tethys realms (western Europe and northern Africa), and biozonations from these areas are the most accurate of the world. Comparatively, investigations in the Pacific realm are scarce, and, in Argentina, they are limited to contributions based on oil-industry subsurface and outcrop reports for the Los Molles Formation. A focused systematic analysis was not previously addressed in the area. The Neuquén Basin in west-central Argentina offers a unique opportunity to study the Early Jurassic calcareous nannofossil history in the south-eastern Pacific Ocean. Calcareous nannofossil assemblages from El Matuasto I section (Los Molles Formation) represent one of the earliest records for the Early Jurassic in the Neuquén Basin and one of the few for the eastern Pacific realm. A detailed systematic analysis allowed the recognition of major bioevents and a comparison with worldwide associations and biostratigraphic schemes. A thorough taxonomic discussion of the Early Jurassic nannofossil species of the Neuquén Basin is presented for the first time. Herein, the taxonomic features of coccoliths recorded in the Neuquén Basin are settled. The age of the calcareous nannofossil assemblages recorded in El Matuasto I is early-late Pliensbachian, covering the NJT4a to NJT4c subzones. Similarities between the Neuquén Basin and localities from the proto-Atlantic region suggest an effective connection between the Pacific and Tethyan basins during the Pliensbachian.